Short Form 36 (SF-36) health survey questionnaire in health-related quality of life assessment in patients with inflammatory myopathies - Almurtada Razok; Jasmine Taylor; Ethan Ritz; Kristin Wipfler; Kaleb Michaud; Didem Saygin (Clinical Medicine, 2025)
Introduction: Idiopathic inflammatory myopathy (IIM) is a group of autoimmune diseases characterised by chronic skeletal muscle inflammation presenting as muscle weakness.1 Given chronic multi-system manifestations of IIM, which include skin rashes, interstitial lung disease, inflammatory arthritis, Raynaud’s phenomenon and myocarditis, these patients frequently experience significant impairment in their health-related quality of life (QoL). Nevertheless, there are currently no validated measures to assess QoL in these patients.2 The use of patient-reported outcome measures (PROMs) has been increasingly encouraged in both the clinical and research setting by the US Food and Drug Administration (FDA) and European Medicines Agency (EMA).3 This study aimed to examine the measurement properties of Short Form (SF)-36 in QoL assessment of adults with IIM. Materials and Methods: FORWARD is a US-based databank collecting biannual patient-reported data on rheumatic diseases, including sociodemographics, symptoms, treatment and health-care utilisation.4 SF-36 produces physical (PCS) and mental (MCS) component scores, ranging from 0 to 100, with higher scores indicating a better QoL.5 Discriminant and construct validity were assessed using proportion of a priori hypotheses. Responsiveness was assessed using linear mixed models. Results and Discussion: A total of 168 patients with IIM were included (77.3% women, 78.5% White), with an average (±standard deviation (SD)) age in years of 54.3 (±13.8). Mean SF-36 PCS and MCS were 36.5 (±11.2) and 47.0 (±12.0), respectively. Mosta priori hypotheses for construct and discriminant validity were met for PCS and MCS. PCS differed between those with low vs high physical function, disease activity, fatigue and pain, while MCS differed between patients with and without depression and anxiety, and low vs high fatigue and pain levels (p<0.0001). Table 1 demonstrates the discriminant validity and compares how SF-36 PCS and MCS differ among subgroups of patients with IIM. PCS and MCS had moderate to strong correlations with pain, fatigue, physical function, disease activity and health satisfaction. Longitudinal changes in these parameters were also significantly associated with changes in PCS and MCS over time. Table 2 examines the relationship between longitudinal change in SF-36 PCS and MCS and other outcome variables after controlling for age, sex and obesity. Conclusion: SF-36 demonstrated adequate discriminant and construct validity and responsiveness for health-related QoL assessment in patients with IIM. This makes SF-36 a very promising tool to assess and monitor health-related QoL in clinical practice and myositis clinical trials.